Rates of unanticipated premalignant and malignant lesions at the time of hysterectomy performed for pelvic organ prolapse in an underscreened populationAJOG MFM at a Glance - Syem Barakzai, MD; Emma Koltun-Baker, BS; Samuel J.F. Melville, BS; Enanyeli Rangel, MD; Molly Dahl, MD; Christina E. Dancz, MD, MPH (Elsevier, 2023)
BACKGROUND: The rate of unanticipated premalignant or malignant pathology at the time of hysterectomy performed for pelvic organ prolapse has been previously reported to be 0.2%. It is not known whether this rate is similar in patients with limited access to regular medical care. OBJECTIVE: This study aimed to describe the rates of unanticipated premalignancy and malignancy at the time of hysterectomy performed for pelvic organ prolapse in an underscreened population and to determine the risk factors for unanticipated pathology. STUDY DESIGN: Hysterectomies performed for pelvic organ prolapse at a large public hospital between July 2007 and July 2019 were reviewed. Patients undergoing surgery for malignancy or premalignancy were excluded. Medical records were reviewed for demographic information, medical history, preoperative workup, and final pathology. Frequencies of abnormal pathologies were calculated. Demographic and screening factors were correlated with pathologic findings using the Fisher exact test or Mann-Whitney U test, as appropriate. This study was approved by the institutional review board. RESULTS: Between 2007 and 2019, 759 cases of pelvic organ prolapse were identified. Of 759 patients, 667 (87.9%) self-identified as Hispanic. The median age was 57 years old, and 505 of 759 patients (66.5%) were in the postmenopausal stage. Abnormal uterine bleeding history was present in 217 of 759 patients (28.6%). Of 759 patients, 493 (65.4%) underwent preoperative ultrasonography, and 290 (38.3%) underwent preoperative endometrial biopsy. Of the 744 uterine specimens that had available histology results, there were 2 cases of endometrial hyperplasia and 1 case of endometrial cancer. Of the 729 cervical specimens that were available for review, there was 1 case of intraepithelial neoplasia and 2 cases of cervical cancer. In the 246 patients who underwent oophorectomy, no ovarian malignancy was found. CONCLUSION: For patients undergoing hysterectomy for pelvic organ prolapse in an underscreened population, the rates of endometrial dysplasia or cancer were 0.40% (3/744), and the rates of cervical dysplasia or cancer were 0.42% (3/729). Our results underscore the importance of considering screening history when interpreting preoperative cervical and endometrial cancer screening. Consideration of higher negative predictive value tests, such as cytology with human papillomavirus cotesting and preoperative counseling on the risks and management strategies of unanticipated premalignancy or malignancy within this population may be reasonable.